Racial and Ethnic Differences in the Transition To a Teenage Birth in the United States. Issue 2 (7th May 2013) - Manlove, Jennifer; Steward‐Streng, Nicole; Peterson, Kristen; Scott, Mindy; Wildsmith, Elizabeth
<x xml:space="preserve">Abstract</x> Context Rates of teenage childbearing are high in the United States, and they differ substantially by race and ethnicity and nativity status. Methods Data from the National Longitudinal Survey of Youth 1997 cohort were used to link characteristics of white, black, U.S.‐born Hispanic and foreign‐born Hispanic adolescents to teenage childbearing. Following a sample of 3, 294 females aged 12–16 through age 19, discrete‐time logistic regression analyses were used to examine which domains of teenagers' lives were associated with the transition to a teenage birth for each racial and ethnic group, and whether these associations help explain racial and ethnic and nativity differences in this transition. Results In a baseline multivariate analysis controlling for age, compared with whites, foreign‐born Hispanics had more than three times the odds of a teenage birth (odds ratio, 3.5), while blacks and native‐born Hispanics had about twice the odds (2.1 and 1.9, respectively). Additional controls (for family environments; individual, peer and dating characteristics; characteristics of first sexual relationships; and subsequent sexual experience) reduced the difference between blacks and whites, and between foreign‐born Hispanics and whites, and eliminated the difference between U.S.‐born Hispanics and whites. Further, if racial or ethnic minority adolescents had the same distribution as did white teenagers across all characteristics, the predicted probability of a teenage birth would be reduced by 40% for blacks and 35% for U.S.‐born Hispanics. Conclusions Differences in the context of adolescence may account for a substantial portion of racial, ethnic and nativity differences in teenage childbearing.